ANALYSIS MANAGEMENT OF THE RALLA MODERN TRADITIONAL MARKET, TANETE RIAJA DISTRICT, BARRU REGENCY - Wahyul AZ Wahyul AZ; Rosdiana; Nurlena (Sean Institute, 2023)
This purpose is to find out the analysis of the Ralla Modern Traditional Market, Tanete Riaja District, Barru Regency the Ralla traditional market, Tanete Riaja District, Barru Regency.The research used is a qualitative research,, method, the source of the data obtained by means of surveys, interviews, observation, documentation. Data analysis of data collection, reduction of data presentation and drawing conclusions.The results of the Ralla Modern Traditional Market Management research show that there is good management, but it is still not optimal. This can be seen from the supervision of the person in charge who still relies on the market in terms of checking facilities, market security, market cleanliness, and collecting retribution from traders, so that inactive members are not visible. This purpose is to find out the analysis of the Ralla Modern Traditional Market, Tanete Riaja District, Barru Regency the Ralla traditional market The research used is a qualitative research method, the source of the data obtained by means of surveys, interviews, observation, documentation. Data analysis of data collection, reduction of data presentation and drawing conclusions.The results of the Ralla Modern Traditional Market Management research show that there is good management, but it is still not optimal. This can be seen from the supervision of the person in charge who still relies on the market in terms of checking facilities, market security, market cleanliness, and collecting retribution from traders, so that inactive members are not visible.